Modeling of Wastewater Sludge Dewatering Kinetics Using the Method of Linear Proportionalities - Orest Verbovskyi; Vadym Orel; Volodymyr Femiak (Energy Engineering and Control Systems)
Sewage sludge accumulating at treatment facilities is aqueous suspensions separated from wastewater during treatment processes. Untreated sludge has been discharged for decades into overloaded sludge beds, dumps, or quarries, leading to environmental safety violations and deteriorating people living conditions. Due to a high content of colloidal substances, sludge poorly releases water. An important step in sludge disposal is dewatering, which significantly reduces sludge volume. Factors such as moisture content, the ratio of free to bound water, the degree of dispersion of solid phase particles, chemical composition, structure, and viscosity significantly influence sludge dewatering. The compressibility of sewage sludge under external pressure is one of its characteristic properties. Modeling was carried out using the method of linear proportions, which allowed the derivation of a uniform functional dependence under different combinations of similarity numbers.